Effects of maternal voice on painful procedures in preterm and full‐term infants: A systematic review and meta‐analysis. Issue 3 (24th June 2022) - Ding, Shenglan; Huang, Xiuhua; Li, Xue; Shen, Yi; Yang, Lili
Abstract: Background: Preterm and full‐term infants are often exposed to painful procedures during their hospitalization and pain management should be implemented. Maternal voice is a kind of non‐pharmacologic pain management strategy. However, the efficacy of maternal voice on painful procedures is unclear. Aims: To evaluate the effects of maternal voice on painful procedures in preterm and full‐term infants. Methods: We conducted a systematic search in PubMed, the Cochrane Central Register of Controlled Trials (CENTRAL), Web of Science, EMBASE, CINAHL, Chinese Biomedical Literature Database and ProQuest Dissertation and Theses from inception to March 2022. Review Manager 5.3 was used for data analysis. Random effects model was used for pooling data and the quality of outcomes was assessed by GRADE evidence profiles. Results: A total of 10 studies were included in this systematic review and meta‐analysis with 323 participants in the intervention groups and 325 in the control groups. The results showed that maternal voice could reduce pain levels during and until 10 min after painful procedures compared with routine care (SMD = −0.78, 95%CI [−1.12, −0.44], Z = 4.44, p  < .00001; SMD = −0.36, 95%CI [−0.66, −0.06], Z = 2.33, p  = .02; SMD = −0.87, 95%CI [−1.40, −0.34], Z = 3.20, p  = .001; SMD = −0.94, 95%CI [−1.48, −0.41], Z = 3.44, p  = .0006; SMD = −1.30, 95%CI [−1.59, −1.01], Z = 8.76, p  < .00001, respectively). Patients in maternal voice group had a lower increase in heart rate during and until 2 min after painful procedures (all p  < .05). Oxygen saturation was significantly higher in maternal voice group during and until 4 min after painful procedures (all p  < .05). The results revealed that maternal voice showed statistically significant effects in respiratory rate and comfort levels during the painful procedures (all p  < .05). Conclusion: This systematic review and meta‐analysis indicated that maternal voice was effective in reducing procedural pain levels. The vital signs of patients in maternal voice group were more stable. Relevance to Clinical Practice: Maternal voice can be used as an effective non‐pharmacologic intervention to alleviate procedural pain for preterm and full‐term infants during their hospitalization. Because the quality of synthesized evidence was 'moderate' to 'very low', larger sample size and high quality studies are warranted.